O império das (nas?) municipalidades: as elites e o governo da cidade no Brasil oitocentista (Recife, 1829-1849) - Souza, Williams Andrade de (Universidade do Vale do Rio dos Sinos, 2019)
This is a study on municipality and city government in nineteenth-century Brazil. Taking Recife's House of Representatives as analysis object between 1829 and 1849, a profile of this institution and its elected and active councilmen was drawn at the period. Based on theoretical and methodological assumptions of elitism, prosopography and microanalysis, and through a varied and extensive documentary collection, political-bureaucratic-administrative-representative characteristics and functions were drawn of municipal entity and trajectory, alliance networks and 95 individuals who exercised elective position in it. Contrasting this reading with Thompsonian perspectives, it was pointed out that municipal administration exercise was based on paternalistic and clientelistic relation logic, advances with the analysis were done; also showing that it was impacted by liberalizing ideological presuppositions in force. At the limit, it was pointed out that city governance was exercised among state legal prerogatives; complex elite interests, which acted in it and its interlocution with social daily. In this triad, the Local House was not only a domination instrument, but also a representative instance with which population could interact and demand their daily needs; thus participating in governing world, dominant elite destinies and formation process and consolidation of Brazilian liberal state in the first half of the nineteenth century.
Keywords: Câmara municipal; Elite municipal; Governo da cidade; Recife; Formação do Estado liberal brasileiro; Século XIX; Elitismo; Prosopografia; Microanálise; City council; Municipal elite; City government; Recife; Formation of Brazilian liberal state; Nineteenth century; Elitism; Prosopography; Microanalysis; ACCNPQ::Ciências Humanas::História